2013
DOI: 10.4103/2229-5178.120646
|View full text |Cite
|
Sign up to set email alerts
|

Benign cephalic histiocytosis

Abstract: A one and a half year old girl born of a non-consanguineous marriage presented with multiple asymptomatic erythematous to hyperpigmented and skin colored papules on both cheeks slowly increasing in number of 1 year duration. On the basis of clinical, histopathological, and immunohistochemistry findings, a diagnosis of benign cephalic histiocytosis was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Patsatsi et al found in 2014 that there had been only 55 reported cases in the English‐language literature since Gianotti et al first described this disorder in 1971. With a few additional cases thereafter, we presume that there have now been nearly 60 reported cases . We have identified 11 BCH cases over the past 12 years at a single center (Table ), suggesting that the disease may be more common than previously thought.…”
Section: Clinical and Demographic Characteristics Of 11 Patientsmentioning
confidence: 79%
“…Patsatsi et al found in 2014 that there had been only 55 reported cases in the English‐language literature since Gianotti et al first described this disorder in 1971. With a few additional cases thereafter, we presume that there have now been nearly 60 reported cases . We have identified 11 BCH cases over the past 12 years at a single center (Table ), suggesting that the disease may be more common than previously thought.…”
Section: Clinical and Demographic Characteristics Of 11 Patientsmentioning
confidence: 79%
“…Histiocytes are often admixed with lymphocytes and a few eosinophils and cells typically express non-Langerhans cell histiocytic markers including CD11b, CD11c, CD14b, CD68 and HAM56. 4,5 The differential diagnosis includes the non-Langerhans cell histiocytosis (non-LCH) disorders, particularly eruptive histiocytoma and juvenile xanthogranuloma, as well as urticaria pigmentosa. Frequently, clinical differentiation is possible, as the number of the lesions as well their distribution pattern mainly in the cephalic region usually allow for distinction of benign cephalic histiocytosis from other non--LCH disorders.…”
Section: Benign Cephalic Histyocitosismentioning
confidence: 99%
“…En general, se trata de pacientes por lo demás sanos; sin embargo, hay dos casos reportados en la literatura asociados a diabetes insípida 64,65 . La mayoría de los casos presentan resolución espontánea en 8 meses a 4 años [61][62][63] .…”
Section: Manifestaciones Clínicasunclassified